Identification of microenvironment‐related genes with prognostic value in clear cell renal cell carcinoma. Issue 7 (21st January 2020) - Zhang, Zhao; Li, Zeyan; Liu, Zhao; Zhang, Xiang; Yu, Nengwang; Xu, Zhonghua
Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common type of kidney tumor. Previous studies have shown that the interaction between tumor cells and microenvironment has an important impact on prognosis. Immune and stromal cells are two vital components of the tumor microenvironment. Our study aimed to better understand and explore the genes involved in immune/stromal cells on prognosis. We used the Estimation of STromal and Immune cells in MAlignant Tumor tissues using Expression data algorithm to calculate immune/stromal scores. According to the scores, we divided ccRCC patients from The Cancer Genome Atlas database into low and high groups and identified the genes which were differentially expressed and significantly associated with prognosis. The result of functional enrichment analysis and protein‐protein interaction networks indicated that these genes mainly were involved in extracellular matrix and regulation of cellular activities. Then another independent cohort from the International Cancer Genome Consortium database was used to validate these genes. Finally, we acquired a list of microenvironment‐related genes that can predict prognosis for ccRCC patients. Abstract : By analyzing the data about clear cell renal cell carcinoma in The Cancer Genome Atlas and International Cancer Genome Consortium databases, we excavated a series of microenvironment‐related genes with prognostic value.